Analisis Pengaruh Inflasi, Ekspor, Impor, dan Nilai Tukar terhadap Cadangan Devisa Negara - Ika Septiana Windi Antari; Muhammad Kholid Al-Zani; Ilham Antony Saputra (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
Foreign exchange reserves are essential for assessing a country's financial stability, especially in countries highly dependent on international trade, such as Indonesia. Various economic factors, including inflation, exports, imports and changes in exchange rates, influence Indonesia's foreign exchange reserves. Domestic inflation is essential in determining a country's currency and stability. If inflation is high, the exchange rate will increase, which in turn will impact the size of the country's foreign exchange reserves. Therefore, controlling inflation is essential in maintaining the stability of foreign exchange reserves. Exports and imports also significantly influence a country's foreign exchange reserves. The higher the exports, it shows that the country is more advanced and can generate foreign exchange reserves. Imports are the opposite of exports. The country's foreign exchange reserves are usually used to make payments for import activities. This means that the country's foreign exchange reserves will decrease further if imports are higher. This research uses time series data from 2010 to 2020, so the analysis used is the Error Correction Model (ECM). Based on the research results, it was found that to increase the country's foreign exchange reserves, it is necessary to increase the value of exports and exchange rate stability and reduce the value of inflation.